Relationship between childhood trauma, neuropsychological deficits, neural circuitry, and anxiety proneness in high-anxiety prone and low-anxiety prone adolescents - Martin, Lindi Imelda (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMed)--Stellenbosch University, 2017.